Multiple Autoimmune Syndromes Including Acute Disseminated Encephalomyelitis, Myasthenia Gravis, and Thyroiditis Following Messenger Ribonucleic Acid-Based COVID-19 Vaccination: A Case Report - Poli, Khouloud; Poli, Sven; Ziemann, Ulf (Frontiers in Neurology, 2022)
The global pandemic has resulted from the emergence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), causing coronavirus disease 2019 (COVID-19). To control the spread of the pandemic, SARS-CoV-2 vaccines have been developed. Messenger ribonucleic acid (mRNA)-based COVID-19 vaccines have been the most widely used. We present the case of a 65-year-old patient, who was diagnosed with acute disseminated encephalomyelitis, ocular myasthenia gravis, and autoimmune thyroiditis, following his third mRNA COVID-19 vaccination. On admission, the patient showed mild left-sided hemiparesis, contralateral dissociated sensory loss, dizziness, and right-sided deafness. Brain MRI revealed multiple acute inflammatory contrast-enhancing periventricular and brainstem lesions with involvement of vestibulo-cerebellar tract and cochlear nuclei. Despite steroid pulse and intravenous immunoglobulin therapy, clinical symptoms and MRI lesions worsened, and additional signs of ocular myasthenia gravis and elevated but asymptomatic thyroid antibodies developed. After repeated plasma exchange, all clinical symptoms resolved. This is, to the best of our knowledge, the first case report of multiple autoimmune syndromes triggered by COVID-19 vaccination. The rare occurrence of such treatable autoimmune complications should not question the importance of vaccination programs during the COVID-19 pandemic.